Optimalisasi Dosis Pupuk Biourine Sapi untuk Meningkatkan Pertumbuhan dan Produksi Pakcoy (Brassica rapa L.) - Anwar, Muhammad; Hidayati, Elwani; Salam, Riza Hamkary (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Biourine fertilizer is a liquid organic fertilizer derived from fermented livestock urine with the help of decomposer materials such as EM4 or MOL. Although potential as a source of nutrients, the use of biourine does not yet have the right dose standards and stable quality. This study aims to determine the effect of various doses of cow biourine fertilizer on the growth and production of pak choy plants, as well as to determine the optimum dose that gives the best results. The study was conducted experimentally in a screen house using polybag media, with a non-factorial completely randomized design (CRD) consisting of five dose treatments: P0 (0 ml/L), P1 (10 ml/L), P2 (20 ml/L), P3 (30 ml/L), and P4 (40 ml/L). Each treatment was repeated five times, resulting in 25 experimental units. The parameters observed included plant height, number of leaves, leaf length, leaf width, and wet compost weight. Data were analyzed using ANOVA at a 5% significance level and a 5% BNJ further test to see the differences between treatments. The results showed that the provision of cow biourine fertilizer had a significant effect on the growth and yield of pak choi. Treatment P2 (20 ml/L) gave the best results in most parameters including plant height, leaf length including the highest wet stalk weight of 77.40 grams which was significantly different compared to other treatments. Thus, a dose of 20 ml/L cow biourine can be recommended as the optimum dose for the growth and yield of pak choi plants